Estudo e implementação de soluções para a melhoria da qualidade de serviço da rede do departamento de informática da FCUL: autentificação baseada e, 802.1X e transição para IPV6 - Broega, António José Carvalho (2012)
Currently, the systems and networks are present in various sectors of society and prove to be of great importance, so it is necessary to protect the network from unauthorized users. Against this background, the first objective of this master’s project is to increase the network security of the Department of Informatics, Faculty of Sciences, University of Lisbon. Several mechanisms to control network access were studied and has been chosen to implement 802.1x authentication because it presents a series of features that makes this the most appropriate solution for the study conditions. With 802.1x authentication is possible to categorize different types of users who have access to different resources provided by the system depending on their profile. The implementation of this solution did not involve any cost to the department. The 802.1x authentication was successfully implemented and is currently available in the department. The second part of this project is dedicated to the study of the existing conditions for a transition to IPv6. With the imminent exhaustion of IPv4 addresses available, it becomes necessary to study the changes that a possible transition could cause in the system (DHCP, DNS, software and hardware) of the department. Several strategies for migrating to IPv6 and the benefits this could bring to the department were studied. In addition, a detailed plan for the transition has been designed.